KETIDAKADILAN GENDER TERHADAP ISTERI PETANI DI KEC. PORTIBI KAB. PALUTA - Santi Marito Hasibuan (IAIN Padangsidimpuan, 2019)
This study aims to identify forms of gender injustice against farmers' wives in Portibi District, Paluta Regency. The method used in this study is a qualitative-phenomenological method, while data collection is done by interview and observation methods. The results of this study concluded that the wife of a farmer in Portibi District experienced gender inequality. Forms of injustice experienced by farmers' wives occur in refroductive work, subordination, double burden, marginalization and domestic violence.Kata Kunci : Ketidakadilan, gender, isteri petani